Ecophysiological Responses of Tall Fescue Genotypes to Fungal Endophyte Infection, Elevated Temperature, and Precipitation. Issue 6 (1st November 2015) - Bourguignon, Marie; Nelson, Jim A.; Carlisle, Elizabeth; Ji, Huihua; Dinkins, Randy D.; Phillips, Tim D.; McCulley, Rebecca L.
ABSTRACT: Tall fescue ( Schedonorus arundinaceus (Schreb.) Dumort., nom. cons.) can form a symbiosis with the fungal endophyte Epichloë coenophiala, whose presence often benefits the plant, depending on plant and fungal genetics and the prevailing environmental conditions. Despite this symbiosis having agricultural, economic, and ecological importance, relatively little is known regarding its response to predicted global climate change. We quantified the ecophysiological responses of four tall fescue genetic clone pairs, where each pair consisted of one endophyte‐infected (E+) and one endophyte‐free clone, to climate change factors of annually elevated temperature and seasonally increased precipitation. Endophyte presence increased fescue tillering and biomass production in the elevated temperature treatment and greatly enhanced the ability of two of the fescue clones to recover from the hot and unusually dry summer. Surprisingly, endophyte infection also stimulated biomass production and photosynthesis rates (for one clone) in the most mesic treatment (additional precipitation). Toxic ergot alkaloid concentrations increased in E+ individuals exposed to elevated temperatures, particularly in the fall, but the strength of the response varied across E+ genotypes. Overall, this study suggests that choice of plant and endophyte genetic material will be important in determining the productivity, toxicity, and resilience of tall fescue pastures under future climate conditions.